Life cycle Spodoptera frugiperda JE Smith with lettuce (Lactuca sativa L.) and pakcoy (Brassica rapa L.) in the laboratory - Ichsan Luqmana Indra Putra; Khusnul khotimah (Department of Plant Protection, Faculty of Agriculture, Universitas Jember - Indonesia, 2021)
Spodoptera frugiperda JE Smith. is a new pest on maize plants in Indonesia and is polyphagous. The purpose of this study is to find out what plants are lettuce and pakcoy can be used as potential hosts for S. frugiperda, its life cycle, sex ratio and number of eggs produced in the laboratory. The research was conducted in October 2019 - January 2020. Treatment and observations were carried out at the Botanical Laboratory, Ahmad Dahlan University. The parameters taken were the average value of larvae length, head diameter, weight of instar larvae 3 - 6, length and weight of pupa, sex ratio, number of eggs, and life cycle length of S. frugiperda. The highest average value of all observed parameters was pakcoy leaves. The length of time needed for one life cycle is the fastest for pakcoy leaves for 37 days. This study showed that lettuce and pakcoy plants could be used as potential hosts with the best growth in the treatment of pakcoy leaves. Keywords: Brassica rapa, Lactuuca sativa, pakcoy , lettuce, S. frugiperda